Limits on quark compositeness from high energy jets in p̄p collisions at 1.8 TeV - Abbott, B; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Akimov, V; Alves, G; Amos, N; Anderson, E; Baarmand, M; Babintsev, V; et al. (2000)
Events in p̄p collisions at √s= 1.8 TeV with total transverse energy exceeding 500 GeV are used to set limits on quark substructure. The data are consistent with next-to-leading order QCD calculations. We set a lower limit of 2.0 TeV at 95% confidence on the energy scale ΛLL for compositeness in quarks, assuming a model with a left-left isoscalar contact interaction term. The limits on ΛLL are found to be insensitive to the sign of the interference term in the Lagrangian. ©2000 The American Physical Society.